2007
DOI: 10.1007/s11267-007-9158-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cell-to-matrix Ratio in Polyvinyl Alcohol Immobilized Pure and Mixed Cultures on Atrazine Degradation

Abstract: Atrazine biodegradation by immobilized pure and mixed cultures was examined. A pure atrazinedegrading culture, Agrobacterium radiobacter J14a (J14a), and a mixed culture (MC), isolated from an atrazine-contaminated crop field, were immobilized using phosphorylated-polyvinyl alcohol (PPVA). An existing cell immobilization procedure was modified to enhance PPVA matrix stability. The results showed that the matrices remained mechanically and chemically stable after shaking with glass beads over 15 days under vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 42 publications
(52 reference statements)
3
28
0
Order By: Relevance
“…This could be from limitation of substrate diffusion in the entrapped cell systems leading to lower treatment efficiencies. Similar situation also reported in previous studies (Kim et al 2001;Song et al 2005;Siripattanakul et al 2008). However in later cycles (3-5), ECSBR (removal of 75 ± 10%) significantly performed superior over SBR (removal of 51.5 ± 11.5%).…”
Section: Sequencing Batch Experiment: Investigation Of Ecsbr and Sbr supporting
confidence: 89%
See 1 more Smart Citation
“…This could be from limitation of substrate diffusion in the entrapped cell systems leading to lower treatment efficiencies. Similar situation also reported in previous studies (Kim et al 2001;Song et al 2005;Siripattanakul et al 2008). However in later cycles (3-5), ECSBR (removal of 75 ± 10%) significantly performed superior over SBR (removal of 51.5 ± 11.5%).…”
Section: Sequencing Batch Experiment: Investigation Of Ecsbr and Sbr supporting
confidence: 89%
“…A previous publication reviewed adsorption ability of entrapment matrices which was commonly found at the early stage of matrix utilization (Siripattanakul and Khan, 2010). In case of the entrapped cell reutilization, no or less adsorption would be observed (Siripattanakul et al 2008). It was clear that the entrapped yeast cell systems successfully reduced glucose by matrix adsorption (glucose immobilization) and biodegradation (glucose bioconversion) but the main process was biodegradation.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…Similar results were observed with mixed cultures [14]. Several studies reported that high amounts of cells inside the matrix lower the space for the diffusion of substrate and other necessary elements and in turn reduce and q [23,33,34]. In addition, the entrapped cells had less space to grow at higher initial cell concentrations (cell-to-matrix ratios).…”
Section: Effect Of Cell-to-matrix Ratiosupporting
confidence: 78%
“…PVA beads were found to be very durable against abrasion and pH variation and no recognizable destruction of bead appearance was observed during several months of operation in previous studies [23,24]. Alginate beads exhibit less durability than PVA beads and stabilization may be necessary to maintain its long-term operational efficiency [1,25,26].…”
Section: Cell Entrapmentmentioning
confidence: 87%
“…Entrapment of spores were also used when Humicola lutea was immobilized in PVA crosslinked via N,N 0 -methylenebisacrylamide with or without added PEG. It Mixed culture Diesel-contaminated soil PVA-cryogel [33] Basic study Atrazine in water PVA-cryogel [34] Analytical applications Glucose analysis Glucose oxidase Enzyme immobilized in albumin/chitosan gel [22] Pseudomonas putida Detection of phenol Clark electrode used for detection [35] Pseudomonas sp.…”
Section: Analysis Of Acetylcholinementioning
confidence: 99%